Role of identified noncoding RNA in erectile dysfunction. (22nd May 2020) - Chen, Sixiang; Sun, Xiaoping; Wu, Suliu; Jiang, Jing; Zhu, Chenfeng; Xu, Kechen; Xu, Keyang
Abstract: Erectile dysfunction (ED) is a common male sexual dysfunction and is closely related to many risk factors such as age, chronic diseases and mental disorder. Phosphodiesterase type 5 inhibitor (PDE5i) is recommended as the first‐line medicine in therapy, but up to 35% of patients fail to this treatment. Unfortunately, the pathogenesis of ED is still poorly understood. Hence, it has reached the state that researchers should seek for new candidate biomarkers or therapeutic targets. Recent studies have reported that noncoding RNAs (ncRNAs) such as microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) are involved in the pathogenesis process of ED, even in stem cell therapy. In this review, we aim to summarise the mechanisms and functions of identified ncRNAs that are associated with ED.